Perspectives on the Effectiveness of Madrid's Regional Bilingual Programme: Exploring the Correlation between English Proficiency Level and Pre-Service Teachers' Beliefs - Lidia Mañoso-Pacheco; Roberto Sánchez-Cabrero (MDPI AG, 2022)
This study aims to examine the opinions of prospective pre-primary and primary teachers about Madrid's regional Bilingual Programme in Spain, assessing the correlations between their self-perceived level of English and their positioning concerning the effectiveness of the regional programme. Although there is a growing body of research in the field of education on how CLIL (Content and Language Integrated Learning) provisions impact in-service teachers' attitudes concerning bilingual education, there is a dearth of literature on the way student teachers depict the teaching reality. Thus, this paper explores pre-service teachers' beliefs towards the Bilingual Programme via an ad hoc questionnaire, administered to a non-probabilistic sample of 170 undergraduate students at the Universidad Autónoma de Madrid. The data collected were explored using Chi-square and Somers' D tests. The results show that the self-perceived English level, greatly determined by prior bilingual schooling, has a strong influence on their perceptions about the Bilingual Programme. The findings also indicate that, although the learning experience at the pre-primary stage is valued positively by students, the acquisition of curricular contents in primary education is seen as negatively affected due to English medium instruction.